PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL SISWA KELAS X MIA SMAN 9 KOTA JAMBI - Endah Fitria; Buyung Buyung; Aisyah Aisyah (Universitas Batanghari Jambi, 2018)
Abstract: This research is motivated by the existence of problems in the preparation of LKS being used in SMA Negeri 9 Kota Jambi. LKS is a teaching material that also plays an important role in improving the quality of learning. Preparation of the appropriate LKS and in accordance with the curriculum used is expected to achieve the learning objectives, so it needs continuous LKS development activities. The purpose of this research is to develop LKS based on Contextual Teaching and Learning (CTL) on linear equation system material three valid, practical and effective variables.This type of research development is Research and Development (R & D) with the ADDIE development model. Stages of the ADDIE development model consist of analysis, Design, Development, Implementation, Evaluation. The research instrument consists of Questionnaire and question instrument. Questionnaires consist of validation sheet by the material expert, validation assessment sheet by design expert, validation assessment sheet by media expert, individualized trial evaluation sheet, small group trial evaluation sheet, and evaluation field test sheet. while the question instrument consists of a pre-test and post-test questions. LKS developed, then validated by the validator. Validation results obtained LKS with revisions based on suggestions and comments validator. Validity is illustrated by the percentage of material expert, designer and media experts in 82,61% in